Consensus of expert through Indian perspective on the fixed-dose combination dapagliflozin and linagliptin combination in type 2 diabetes mellitus: CONSEPDT study - Gangopadhyay, Kalyan K.; Sharma, Anil; Kumar, Arun; Mehta, Ashwani; Mohan, Jagdish C.; Malige, Manjunatha; Kumar, Rajesh B.; Mittal, Rajneesh; Singh, Santosh K.; Singh, Shailendra K.; Shaikh, Shehla S.; Malhotra, Vinay; et al. (International Journal of Research in Medical Sciences, 2025)
Effective management of type 2 diabetes mellitus (T2DM) increasingly demands a shift from a glucose-centric model to a comorbidity-centric approach, particularly in populations with high cardio-renal risk profiles. The fixed-dose combination (FDC) of dapagliflozin, a sodium-glucose co-transporter-2 inhibitor (SGLT2i), and linagliptin, a dipeptidyl peptidase-4 inhibitor (DPP4i), presents a synergistic, safe, and effective treatment option for patients with complex comorbidities. This combination not only improves glycemic control but also offers pleiotropic benefits, such as weight neutrality and reduced risk of hypoglycemia. Despite robust clinical evidence supporting its efficacy and safety, the absence of standardized, region-specific guidelines has led to inconsistent adoption in clinical practice across India. A consensus tailored to Indian clinical settings is necessary to ensure rational, evidence-based, and uniform use of this FDC. Such a framework will assist healthcare providers in making informed decisions, improving adherence, minimizing complications, and ultimately enhancing patient outcomes. The consensus aims to harmonize diabetes management by incorporating global evidence into local clinical practice.